The Impact of Organizational Culture, and Work Motivation on Employee Performance Through Employee Job Satisfaction PT. Kasmar Tiar Raya - Pallawagau, Andi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
The purpose of this research is to examine the direct influence of Organizational Culture and Work Motivation directly and indirectly on Employee Performance. Sample of 120 employees. Data analysis techniques using SEM resulted that organizational culture has a positive effect on employee performance. Work motivation has a positive effect on Employee Performance. Organizational Culture has a positive effect on employee Job Satisfaction. Work motivation has a positive attitude towards employee job satisfaction. Job Satisfaction has a positive effect on the Employee Performance of PT Kasmar Tiar Raya. Perusahaan always maintains and aligns the Role of Organizational Culture in the life of the company's activities and focused on the interests and objectives of the company to improve the performance of employees and must be sensitive to things that can improve work motivation.